Heterotopia and Postmodern Community in the Context of Migration and Relationship Towards Migrants - Kovačević, Vlaho; Malenica, Krunoslav (Italian Sociological Review, 2021)
This work approaches the issue of migration of the Arab population to Europe within the idea of postmodern community and the concept of heterotopia. The social and historical context (of globalization and migration) imposes necessity to discuss the community and postmodern circumstances. In this paper we refer to Foucault’s heterotopic elements within the context of migrations; places of refuge, shelters and migrants’ asylums present certain heterotopias of our society; absolute other places that give a mirror-like mixing experience. Our analysis shows how the underlying motives for resolving some of the key social problems of contemporary Europe and new community formation are not (just) at the level of social forms, but in the vital transformation of people, their lives and relations towards the Other.